Analisis Pertumbuhan Ekonomi, Inflasi, Investasi di Indonesia Terhadap Kesejahteraan Sosial Pada Tahun 2024 - Baba, Bintang Ridzky Arghazora; Paco, Ruben Ewaldo; Teguh, Caleb Andryan; Roe, Muhammad Jonah Putra; Satya, Jonathan Owen (Media Akuntansi dan Perpajakan Indonesia (MAPI), 2026)
Public welfare is a crucial indicator for measuring the success of a nation's development. Development can be measured through economic growth and improvements in the quality of life of the population, as reflected in the Human Development Index (HDI). This study aims to analyze the influence of economic growth, inflation, and investment on social welfare in Indonesia in 2024. This study implemented a quantitative approach utilizing secondary data collected from the Statistics Indonesia (BPS) and the Investment Coordinating Board (BKPM) in 38 provinces. The analytical method used was multiple linear regression, with classical assumption testing to ensure model feasibility, and robust standard errors to increase the reliability of the estimation results. The findings simultaneously demonstrate that economic growth, inflation, and investment significantly influence social welfare. Partially, inflation negatively impacts social welfare, indicating that price increases can suppress people's purchasing power and impact quality of life. Conversely, investment positively impacts the social welfare by encouraging job creation and increased economic activity. Meanwhile, economic growth has proven to be insignificant in terms of social welfare. Therefore, development policies need to be directed at increasing economic growth, while simultaneously controlling inflation and improving the quality of investment to ensure more equitable and sustainable human development.